Besoyong Dalam Pesta Adat Belian Paser Nondoi di Kabupaten Penajam Paser Utara Kalimantan Timur - Retno Kristanti (Institut Seni Indonesia Yogyakarta, 2018)
Besoyong is derived from the word soyong which means the spell or prayers, then besoyong means speaking or singing the spell. Besoyong is usually used by Paser tribe as the media to speak to the ancients spirits and Sangiyang through their daily lives. Besoyong has started to be sung in Traditional Festival of Belian Paser Nondoi once a year at Penajam Paser Utara regency, East Kalimantan. This research explains about presentations form of besoyong continue with internal and external incentive factors of besoyong presence in Traditional Festival of Belian Paser Nondoi. This research uses the theory of Alvin Boskoff about internal and external’s factors of social change applied as internal and external incentive factors of besoyong presence in Traditional Festival Belian Paser Nondoi. Besoyong can be presented individually and also with ensemble. Internal incentive factors of besoyong presence are to elude from evil ghosts, as the mean to invoke clear weather for the festival, as the mean of healing and ast the mean of asking blessing. External incentive factors of besoyong presence are to elevate the district economics & tourism, and to be functioned as the identity of this region.